Television works like this - Bendick, Jeanne (McGraw-Hill, 1965)
Describes television transmitting equipment, including cameras, lights, the control room, relays, and antennas; television programming, videotape and special effects; and special uses of television in sports, news events, commercials, educational television, and closed circuit and pay TV.